BCP crystals promote chondrocyte hypertrophic differentiation in OA cartilage by sequestering Wnt3a. Issue 7 (5th May 2020) - Bertrand, Jessica; Kräft, Tabea; Gronau, Tobias; Sherwood, Joanna; Rutsch, Frank; Lioté, Frédéric; Dell'Accio, Francisco; Lohmann, Christoph H; Bollmann, Miriam; Held, Annelena; Pap, Thomas
Abstract : Objective: Calcification of cartilage with basic calcium phosphate (BCP) crystals is a common phenomenon during osteoarthritis (OA). It is directly linked to the severity of the disease and known to be associated to hypertrophic differentiation of chondrocytes. One morphogen regulating hypertrophic chondrocyte differentiation is Wnt3a. Methods: Calcification and sulfation of extracellular matrix of the cartilage was analysed over a time course from 6 to 22 weeks in mice and different OA grades of human cartilage. Wnt3a and ß-catenin was stained in human and murine cartilage. Expression of sulfation modulating enzymes (HS2St1, HS6St1) was analysed using quantitative reverse transcription PCR (RT-PCR). The influence of BCP crystals on the chondrocyte phenotype was investigated using quantitative RT-PCR for the marker genes Axin2, Sox9, Col2, MMP13, ColX and Aggrecan. Using western blot for β-catenin and pLRP6 we investigated the activation of Wnt signalling. The binding capacity of BCP for Wnt3a was analysed using immunohistochemical staining and western blot. Results: Here, we report that pericellular matrix sulfation is increased in human and murine OA. Wnt3a co-localised with heparan sulfate proteoglycans in the pericellular matrix of chondrocytes in OA cartilage, in which canonical Wnt signalling was activated. In vitro, BCP crystals physically bound to Wnt3a. Interestingly, BCP crystals were sufficient to induce canonical Wnt signalling as assessed by phosphorylation of LRP6 and stabilisation of β-catenin, and to induce a hypertrophic shift of the chondrocyte phenotype. Conclusion: Consequently, our data identify BCP crystals as a concentrating factor for Wnt3a in the pericellular matrix and an inducer of chondrocyte hypertrophy.